Notice that on the second step, we have the following:
![\begin{gathered} -2(x-7)=6 \\ +2\text{ +2} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/5hzt0z4siml3jrd6zrdpj86sss3nv3fgey.png)
in this case, the -2 is multiplying x-7, then to eliminate it, we have to divide by 2 both sides of the equation.
if we divide by -2, we have the following:
![\begin{gathered} -2(x-7)=6 \\ \Rightarrow x-7=(6)/(-2)=-3 \\ \Rightarrow x-7=-3 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/svct5gtzd5ubqspg1o6bok60eec8e8h21a.png)
finally, if we add7 on both sides, we get:
![\begin{gathered} x-7+7=-3+7 \\ \Rightarrow x=4 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/7rf0qoqwfx9hvxvzkqlq35dxr7gflqeoga.png)
therefore, x = 4